Anatomic total shoulder arthroplasty in rheumatoid arthritis: A systematic review. (April 2022) - Haleem, Ahmed; Shanmugaraj, Ajaykumar; Horner, Nolan S.; Leroux, Timothy; Khan, Moin; Alolabi, Bashar
Purpose: Given the poor soft-tissue quality in rheumatoid arthritis patients, many believe that rheumatoid arthritis should be treated with reverse total shoulder arthroplasty (rTSA). The purpose of this paper is to systematically assess outcomes of anatomic total shoulder arthroplasty (aTSA) in rheumatoid arthritis to determine if aTSA remains a viable option. Methods: A comprehensive literature search was conducted identifying articles relevant to aTSA in the setting of rheumatoid arthritis with intact rotator cuff. Outcomes include clinical outcomes and rates of complication and revision. Results: Ten studies were included with a total of 279 shoulders with mean follow-up of 116 ± 69 months. The mean age was 68 ± 10 years. Survivorship was 97%, 97% and 89% at 5, 10 and 20 years, respectively. The overall complication rate was 9%. Radiolucency was present in 69% of patients, of which 34% were at risk of loosening at 79 months. The overall rate of revision was 8.4%. Studies generally reported clinically significant improvements in range of motion, Constant score and ASES score. Conclusion: aTSA in the rheumatoid patient results in improvements in range of motion and patient-reported outcomes. Rates of complications and survivorship are generally good in this population. However, it should be noted that there is significant heterogeneity in outcome reporting amongst the literature on this topic and that many studies fail to adequately report complication and revision rates. When compared to rTSA in patients with rheumatoid arthritis, evidence suggests that aTSA is still a viable treatment option despite the shift in utilization to rTSA.